Fatigue after spinal cord injury: a systematic review of self-assessment instruments/ Aminatun Nabihah Rahman, Aliff Latir, Haidzir Manaf - Rahman, Aminatun Nabihah; Latir, Aliff; Manaf, Haidzir (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Fatigue is one of the consequences of population with spinal cord injury (SCI). A number of instruments measuring fatigue have been developed, but it lacks consistency among SCI participants. The intention of this review is therefore to determine which fatigue scales should be recommended for future research among the SCI population. Data sources included PubMed, Web of Science, and Scopus. The included studies were obligated to use the self-assessment fatigue scale to measure fatigue among participants of SCI, be in the English (Malaysia) language, among human, and full-text articles. Nineteen studies with a total of 8 fatigue instruments were identified and included in this review; Fatigue Severity Scale (FSS), Modified Fatigue Impact Scale for SCI (MFIS-SCI), Modified Fatigue Impact Scale Abbreviation Version (MFIS-5), Fatigue Questionnaire (FQ), Chalder Fatigue Scale (CFQ), Checklist Individual Strength (CIS), Numerical rating scale (NRS) and Visual Analog Scale (VAS). Participants varied from acute, sub-acute and chronic SCI, with traumatic SCI higher than non-traumatic SCI and also varies from Grade A to D classification of AIS. Among all the self-assessment fatigue instruments identified, FSS seems to have the most substantial evidence to be used among the SCI population in measuring fatigue. MFIS-SCI also seems to be able to be more precise in measuring fatigue with multidimensional criteria but still need to have more research on the scale.